Hypoalbuminaemia segregates different prognostic subgroups within the refined standard risk acute graft‐versus‐host disease score. (18th January 2018) - Kharfan‐Dabaja, Mohamed A.; Sheets, Kyle; Kumar, Ambuj; Murthy, Hemant S.; Nishihori, Taiga; Tsalatsanis, Athanasios; Mina, Alain; Mathews, John; Ayala, Ernesto; Chavez, Julio; Perez, Lia E.; Betts, Brian C.; et al.
Summary: Hypoalbuminaemia has been previously described to predict worse non‐relapse mortality (NRM) and inferior overall survival (OS) in allogeneic haematopoietic cell transplant (allo‐HCT) recipients. Here, we evaluate the role of hypoalbuminaemia (<35 g/l) at time of onset of acute graft‐versus‐host disease (aGVHD) when incorporated into the refined aGVHD score. The study population consisted of 522 patients, median age 53 (18–75) years, who underwent an allo‐HCT mostly for haematological malignancies. Standard risk (SR) aGVHD comprised 467 patients (89%) and the number of high risk (HR) cases was 55 (11%). Median follow‐up for all surviving patients was 26 (3–55) months. Two‐year OS was significantly better in patients with SR aGVHD with a serum albumin ≥35 g/l compared to SR with albumin <35 g/l [70% (95% CI = 64–76%) vs. 49% (95% CI = 42–56%), P  < 0·0001]. Also, patients with SR aGVHD and a serum albumin level of ≥35 g/l had a significantly lower NRM at 1‐year post‐transplantation [6% (95% CI = 3–10%) vs. 25% (95% CI = 20–32%), P  < 0·0001]. After our findings are validated in a large cohort of patients, we propose that hypoalbuminaemia should be incorporated into the refined aGVHD risk score to further its ability to predict outcomes within this group.